PENGARUH PROMOSI, STORE ATMOSPHERE, DAN KEMUDAHAN PEMBAYARAN TERHADAP IMPULSE BUYING (Studi Kasus Matahari Department Store Java Supermall Semarang) - Muhammad Aji Pratama; Saryadi Saryadi (Jurnal Ilmu Administrasi Bisnis, 2018)
Impulse buying is a condition that occurs when individuals experience the feeling distressed, suddenly that cannot be countered. There are several factors that affect the impulse buying, among other characteristics such as low product prices, characteristics of marketing such as advertising, material to be discounted at the position, and the goods on display, and characteristics circumstantial as personalities, and consumer demographic. Research on the problem this time around is occurs a decrease in the number of transactions amounted to 9.8% and consumer traffic to 4.4% in Matahari Department Store Java Supermall Semarang year 2016. It is contrary to the purpose of the company in the conduct of the promotion, store atmosphere and ease of payment in order to attract consumers to buy. The purpose of this research is to know the influence of promotions, store atmosphere, and ease of payment against impulse buying either partially or simultaneous. The research results showed that all the independent variables have a positive affect toward the dependent variable, either partially or simultaneous showed the existence of a variable influence promotions, store atmosphere, and ease of pemabayaran against impulse buying. While the views of multiple regression test, the variable has the largest value of the promotion or the strongest value of beta of 0.429, followed by a variable store atmosphere with a beta value of 0.322, and ease of payment with variable values of beta 0.256. From this research are expected to maintain the company's promotion is done. This is because at this time the research, promotion variables have the greatest value or the strongest compared to two other variables, so that by enhancing the promotion of consumer interests can trigger buy especially unplanned purchases (impulse) on the producing company.